Potential for the development of Taraxacum mongolicum aqueous extract as a phytogenic feed additive for poultry - Dong, Zhen; Liu, Zhiqin; Xu, Yufeng; Tan, Bin; Sun, Wenqing; Ai, Qin; Yang, Zihui; Zeng, Jianguo (Frontiers in Immunology, 2024)
The study aimed to assess the potential of TM aqueous extract (TMAE) as a substitute for poultry AGPs. A total of 240 one-day-old Arbor Acker broilers were randomly assigned to four groups and fed a basal diet (Con) supplemented with 500, 1000, and 2000 mg/kg TMAE (Low, Medium, and High groups). The growth performance of the broilers was measured on day 21 and day 42. At the end of the trial, the researchers measured slaughter performance and collected serum, liver, spleen, ileum, and intestinal contents to investigate the effects of TMAE on serum biochemistry, antioxidant capacity, immune function, organ coefficient, intestinal morphology, flora composition, and short-chain fatty acids (SCFAs). The results showed that broilers treated with TMAE had a significantly higher average daily gain from 22 to 42 days old compared to the Con group. Various doses of TMAE resulted in different levels of improvement in serum chemistry. High doses increased serum alkaline phosphatase and decreased creatinine. TMAE also increased the antioxidant capacity of serum, liver, and ileum in broilers. Additionally, middle and high doses of TMAE enhanced the innate immune function of the liver (IL-10) and ileum (Occludin) in broilers. Compared to the control group, the TMAE treatment group exhibited an increase in the ratio of villi length to villi crypt in the duodenum. TMAE increased the abundance of beneficial bacteria, such as Alistipes and Lactobacillus, while reducing the accumulation of harmful bacteria, such as Colidextracter and Sellimonas. The cecum's SCFAs content increased with a medium dose of TMAE. Supplementing broiler diets with TMAE at varying doses enhanced growth performance and overall health. The most significant benefits were observed at a dose of 1000 mg/kg, including improved serum biochemical parameters, intestinal morphology, antioxidant capacity of the liver and ileum, immune function of the liver and ileum, and increased SCFAs content. Lactobacillus aviarius, norank_f_norank_o__Clostridia_UCG-014, and Flavonifractor are potentially dominant members of the intestinal microflora. In conclusion, TMAE is a promising poultry feed additive and 1000 mg/kg is an effective reference dose.